The Potential of Snake Plant (Sansevieria trifasciata) Extract as an Anti-Pollution Product - Proboningtyas, Endah; Dian Roqobih, Fikky (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2025)
Air pollution is one of the major environmental issues that directly affects human health, particularly in enclosed spaces with limited air circulation. Several studies have shown that indoor air contaminant levels are often higher than those found outdoors. Meanwhile, the use of conventional air filtration devices tends to be expensive and less environmentally friendly. This article aims to evaluate the effectiveness of Sansevieria trifasciata (commonly known as snake plant) in reducing indoor air pollution through a literature review approach. The review involved the examination of 15 scientific articles from national and international journals. After screening based on inclusion criteria, 11 articles were selected for further analysis. The results indicate that Sansevieria trifasciata can reduce carbon monoxide (CO) levels by up to 84.18%, absorb formaldehyde up to 30%, and capture other harmful compounds such as benzene and ammonia. These findings suggest that the snake plant has the potential to serve as a natural, economical, and sustainable solution for improving indoor air quality.